DEVELOPMENT OF Chrysomya albiceps WIEDEMANN, 1819 (DIPTERA: CALLIPHORIDAE) AND Musca domestica LINNAEUS, 1758 (DIPTERA: MUSCIDAE) REARED TOGETHER IN PIG TISSUES. - Chaves, Cíntia de Campos; ,Ferreira, Manuela Campos; Mendes, Júlio (Revista de Patologia Tropical / Journal of Tropical Pathology, 2019)
Chysomya albiceps and Musca domestica are important for forensic entomology, and human and animal health. This study analyzed the effects of the coexistence of C. albiceps and M. domestica reared in four different assays in two pig tissues, brain and intestine: assay 1, interaction between the larvae of the same age; assay 2, interaction between larvae of C. albiceps 24 hours older than larvae of M. domestica; assay 3, interaction between larvae of M. domestica 24 hours older than the larvae of C. albiceps; assay 4, larvae of both species were reared together in flasks with a small supply of food. Weight of larvae, growth time and imago emergence frequency were studied. C. albiceps responded better than M. domestica under most conditions tested. Larvae of C. albiceps responded better in mixed cultures (together with M. domestica) than in pure cultures (larvae of the same species). In contrast, M. domestica responded better when reared in pure cultures. Both species presented shorter growth times when their larvae were reared in intestine tissue with larvae 24 hours younger than the larvae of the concurrent species, compared to their respective growth times in pure cultures. The results confirmed that trophic interactions are relevant to the successful colonization of carrion by C. albiceps. Coexistence of the two species may result in changes in values of their biological components. The results also help to shed light on the biology of the two species in carrion.